The Antidiabetic Mechanisms of Cinnamon Extract: Insights from Network Pharmacology, Gut Microbiota, and Metabolites - Rong Wang; Kuan Yang; Xuefeng Liu; Yiye Zhang; Yunmei Chen; Nana Wang; Lili Yu; Shaojing Liu; Yaqi Hu; Bei Qin (Current Issues in Molecular Biology, 2025)
The progression of type 2 diabetes mellitus (T2DM) is shaped by a multifaceted interplay among genetic, behavioral, and environmental factors, alongside gut dysbiosis. Cinnamon, being abundant in polyphenols and flavonoids, shows significant antioxidant effects. Studies have substantiated that cinnamon contributes to the management of glucose and lipid metabolism. However, the anti-diabetic efficacy of cinnamon is not completely understood. The objective of this research was to clarify the anti-diabetic mechanism associated with cinnamon extract through a combination of chemical profiling, network pharmacology, and in vivo investigations. The results indicated that 32 chemical ingredients, including quercetin, were identified through UPLC-Q-TOF-MS. Network pharmacology revealed that 471 targets related to 14 compounds were screened. The analysis of GO enrichment revealed that the primary pathways were notably enhanced in the metabolism of insulin and glucose. In vivo analyses showed that cinnamon could effectively alleviate hyperglycemia, insulin resistance, and lipid metabolism abnormalities via increased relative abundance of Akkermansia and Ligilactobacillus at the genus level and a decreased Firmicutes/Bacteroidetes ratio at the phylum level. Moreover, cinnamon reduced the serum levels of lipopolysaccharide (LPS) and proinflammatory cytokines (IL-6 and TNF-α) and significantly increased the colon Zonula occludens-1 (ZO-1) and occludin protein levels. It was also observed that cinnamon improved the fecal SCFA levels (acetic, propionic, butyric, valeric and caproic acid), while also modifying the bile acid (BA) profile and increasing the conjugated-to-unconjugated BA ratio. The Western blotting analysis further demonstrated that cinnamon activated intestinal FXR/FGF15 and hepatic PI3K/AKT signaling pathways. In summary, the finding confirmed that cinnamon ameliorated glucose and lipid metabolism disorders by safeguarding the intestinal barrier and modulating the gut microbiota and metabolites, thereby activating intestinal FXR/FGF15 and hepatic PI3K/AKT signaling pathways.